The Contribution of the Role of Farmer Family Housewives to the Fulfillment of Family Life - Kaseng, Ernawati Syahruddin (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2024)
The purpose of the research article is to describe the contribution of the dual role of housewives of farm families in improving family welfare, and the efforts underlying IRT's dual role in the public and domestic spheres. The research method used is qualitative descriptive method. Primary data retrieval techniques are through observation, in-depth informant interviews, and secondary data are retrieved through documentation tracking. The non-probality sampling technique was used and then purposive sampling was drawn, based on several criteria to see the contribution of the dual role of farmer wives in increasing income as housewives. The research output of the article shows that the dual role of IRT farming families in the public sphere, such as participating in making a living by working with their husbands in cultivating their farm land to earn income, both money and goods in order to meet family needs. Meanwhile, the dual role of IRT for farming families in the domestic realm, namely in terms of supporting family welfare needs, by managing family needs every day, and doing household chores such as taking care of children and husbands, cooking, washing and so on. Then the obstacles faced by the dual role of IRT farming families to improve their family welfare, including lack of employment, lack of human resources, and minimal level of education and capital, and the development of technology that replaces human labor.